A cross-sectional comparison of the prevalence of obstructive sleep apnea symptoms in adults with down syndrome in Scotland and Japan - Hill, EA; Sawatari, H; Nishizaka, MK; Fairley, DM; Chishaki, A; Funakoshi, K; Riha, RL; Ando, S-I (American Association on Intellectual and Developmental Disabilities, 2020)
Small studies in Western populations report a high prevalence of obstructive sleep apnea (OSA) in adults with Down syndrome. To date, ethnic differences have not been explored. A questionnaire sent to 2,752 adults with Down syndrome aged ≥16 years in Scotland and Japan (789 valid responses) estimated OSA prevalence based on reported symptoms. Symptoms were common in both countries, with snoring (p = 0.001) and arousals (p = 0.04) more prevalent in Japan. Estimated OSA prevalence in adults with Down syndrome was similar in the two countries, and raised in comparison with the general adult population (19.6% in Scotland and 14.3% in Japan; p = 0.08), though BMI was a confounder. Identification and treatment of OSA is recommended in adults with Down syndrome, regardless of ethnicity.